2014
DOI: 10.1111/phn.12174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nursing Interventions Designed to Impact Knowledge, Behaviors, and Health Outcomes for Rural African‐Americans: An Integrative Review

Abstract: Public health nurses are uniquely qualified to assist in the national goals of eliminating health disparities for population groups at risk for poor health outcomes by the development and implementation of evidence-based health promotion interventions. Assisting healthy individuals within community settings reduce risk factors for cardiovascular disease and cancer can potentially decrease mortality rates associated with these diseases and improve health equity for disadvantaged populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Study participants reported higher incomes and educational levels, as well as higher self-reported health literacy rates than national averages. Previous studies have linked higher education levels with higher health knowledge [15][16][17][18]. The lack of Zika knowledge among the educated respondents from this study confirms the continued need for improved education for future professionals about Zika and other public health issues.…”
Section: Discussionsupporting
confidence: 54%
“…Study participants reported higher incomes and educational levels, as well as higher self-reported health literacy rates than national averages. Previous studies have linked higher education levels with higher health knowledge [15][16][17][18]. The lack of Zika knowledge among the educated respondents from this study confirms the continued need for improved education for future professionals about Zika and other public health issues.…”
Section: Discussionsupporting
confidence: 54%
“…Public health cancer intervention research conducted by nurses has often focused on the individual‐level, typically attempting to influence modifiable behaviors (Abbott, ) or diminish direct exposure to carcinogens (Larsson, ; Villareal, ); similarly, precision medicine focuses on intervening at a micro‐individual, genomic level. Little public health nursing research has focused on built and social environment stress exposures that influence genomes and their resulting effects on cancer.…”
mentioning
confidence: 99%